2002
DOI: 10.1071/ah020052
|View full text |Cite
|
Sign up to set email alerts
|

The effects of increased market competition on hospital services in Shandong and Henan Provinces

Abstract: The Chinese government began a major reform of the hospital sector in the early 1980s. The main aim was to increase productivity by phasing out prospective global budgets from the government, and encouraging between-hospital competition for the business of user-pay and insured patients. This goal was to be achieved without unreasonable prejudice to the financial sustainability of hospitals or to the fairness of access and service provision. We explored the effects of these changes by analysing data for four le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Finally, hospital autonomy may run the risk of fragmenting the health system into independent units and displacing essential activities such as basic curative care, public health programs, and other services that are unable to attract private fee-paying patients as more successful autonomous hospitals reallocate resources to high-revenue clinical services (6). Hospitals in more prosperous regions are also in a better position than hospitals in less prosperous regions to take advantage of greater operational and financial autonomy to access private financial resources and to provide "elective" services either through private wards/clinics or within public wards for fee-paying patients (8,34). As such, financial autonomy may indeed undermine the delivery of core services, diminishing integration of the hierarchy of care and breaking up the coherence of the delivery system.…”
Section: Hospital Autonomy In Developing Countriesmentioning
confidence: 99%
“…Finally, hospital autonomy may run the risk of fragmenting the health system into independent units and displacing essential activities such as basic curative care, public health programs, and other services that are unable to attract private fee-paying patients as more successful autonomous hospitals reallocate resources to high-revenue clinical services (6). Hospitals in more prosperous regions are also in a better position than hospitals in less prosperous regions to take advantage of greater operational and financial autonomy to access private financial resources and to provide "elective" services either through private wards/clinics or within public wards for fee-paying patients (8,34). As such, financial autonomy may indeed undermine the delivery of core services, diminishing integration of the hierarchy of care and breaking up the coherence of the delivery system.…”
Section: Hospital Autonomy In Developing Countriesmentioning
confidence: 99%
“…3,5,6 Others suggest that it incents the delivery of unnecessary treatments. [7][8][9] The impact of increased competition on various patient outcomes has been explored in the literature. A systematic review conducted by Léonard et al 10 found that physician density, measured by the physician-to-population ratio, was positively associated with healthcare consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Some believe that it improves performance by enhancing the quality of care delivered, while at the same time, reducing cost . Others suggest that it incents the delivery of unnecessary treatments . The impact of increased competition on various patient outcomes has been explored in the literature.…”
Section: Introductionmentioning
confidence: 99%